Strategi Pengembangan Dan Pengelolaan UMKM Desa Kalikidang Banyumas Jawa Tengah - Dyah Handayani Dewi; Irma Setyawati; Subur Karyatun; Anugrah Rega Setiawan; Muhammad Naufal Hardianto; Ahya Zulfikar (Universitas Darul Ulum, 2023)
Small and Medium Enterprise (SME) is a form of source of money for rural communities. Development and management are needed in running SMEs. However, there are still a few villagers who do not understand how to develop and manage SMEs. Where the SMEs they have been very feasible and good to be widely marketed, such as the people of Kalikidang Village, Banyumas, Central Java, who have various types of SMEs that are worth knowing about. Therefore, this activity aims to provide socialization and understanding regarding how to develop and manage SMEs so that these business activities can grow and develop and compete with products on the market today.